Controls of nitrogen cycling evaluated along a well‐characterized climate gradient. Issue 4 (3rd April 2017) - von Sperber, Christian; Chadwick, Oliver A.; Casciotti, Karen L.; Peay, Kabir G.; Francis, Christopher A.; Kim, Amy E.; Vitousek, Peter M.
Abstract: The supply of nitrogen (N) constrains primary productivity in many ecosystems, raising the question "what controls the availability and cycling of N"? As a step toward answering this question, we evaluated N cycling processes and aspects of their regulation on a climate gradient on Kohala Volcano, Hawaii, USA. The gradient extends from sites receiving <300 mm/yr of rain to those receiving >3, 000 mm/yr, and the pedology and dynamics of rock‐derived nutrients in soils on the gradient are well understood. In particular, there is a soil process domain at intermediate rainfall within which ongoing weathering and biological uplift have enriched total and available pools of rock‐derived nutrients substantially; sites at higher rainfall than this domain are acid and infertile as a consequence of depletion of rock‐derived nutrients, while sites at lower rainfall are unproductive and subject to wind erosion. We found elevated rates of potential net N mineralization in the domain where rock‐derived nutrients are enriched. Higher‐rainfall sites have low rates of potential net N mineralization and high rates of microbial N immobilization, despite relatively high rates of gross N mineralization. Lower‐rainfall sites have moderately low potential net N mineralization, relatively low rates of gross N mineralization, and rates of microbial N immobilization sufficient to sequester almost all the mineral N produced. Bulk soil δ 15 N also varied along the gradient, from +4‰ at high rainfall sites to +14‰ at low rainfall sites, indicating differences in the sources and dynamics of soil N. Our analysis shows that there is a strong association between N cycling and soil process domains that are defined using soil characteristics independent of N along this gradient, and that short‐term controls of N cycling can be understood in terms of the supply of and demand for N.